The present state of Shariah governance of Islamic banks in Bangladesh: an overview - Alam, Md. Kausar; Ahmad, Abu Umar Faruq (al-Uqud : Journal of Islamic Economics, 2025)
This review aims to explore the Shariah governance (SG) scenario of Islamic banks (IBs) in Bangladesh. The review finds that Bangladesh has a lacking of comprehensive SG guidelines, and Islamic banks are practicing guidelines developed by their own. As a result, their SG practices are diversified and create confusion among the stakeholders. Thus, this review overlooked the SG, and summarized the Centralized Shariah Governance Framework (CSGF) and Shariah Secretariat (SR) for the development of existing practices. If the regulatory authorities implement these frameworks within the central bank and Islamic banks, the scenario of SG will be improvized and enhance the trust of stakeholders.